Peningkatan Kemampuan Penggunaan Alat Peraga bagi Guru melalui Bimbingan Teknis Supervisi di MI Yappi Ngrati - Yuriah (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to determine the ability of teachers to use teaching aids through individual guidance activities at MI Yappi Ngrati for the 2020/2021 school year. This study uses an action research method that is carried out through two cycles. Each cycle includes planning, action, observation, and reflection activities. The results showed a significant increase in the ability of teachers to use teaching aids. This is evidenced by the results of the average percentage of teachers who reached 41.50% in the initial data increased to 60.66% in cycle 1 and increased to 72.33% in cycle 2. Individual guidance activities can be applied to madrasah teachers to improve their ability to manage and create a pleasant learning atmosphere through the use of teaching aids.